The Politics of Exploitation and Oppression, British Colonization, and Chinese Involvement in Zimbabwe - Takudzwa, Munhuweyi Kenneth (International Journal of Criminology and Sociology, 2022)
In an analog philosophy by Lobengula of the chameleon and the fly, he unveiled the British occupation of Zimbabwe, which I equally translated or is similar to the 21st-century Chinese involvement in Zimbabwe. In understanding the exploitative nature of colonial and post-colonial politics, the research offered a comparative analysis of the British and Chinese involvement in Zimbabwe. The post-colonial economic colonization neo-colonialism, similar to dependency theory proponents, found the African continent under exploitation and oppression in her post-independence. The researcher utilized qualitative research of documentary review, online sources, and virtual ethnography to unveil and enrich the study phenomenon.